Pediatric forensic evidence : a guide for doctors, lawyers and other professionals - Robinson, David L. (Springer, 2017)
This book provides guidance to all professionals working with children who present with injuries, neglect, illness falsification and other forms of child abuse. Clinical findings and the current literature are analyzed. The author's clinical experience is shared to assist the reader in diagnosing the cause of injury and other presentations. This text is the result of many years of experience in the UK working with children in an East London hospital (which receives over 1000 children a week through the children's Emergency Department) and the analysis of over 400 cases for the Family and Crown Courts. Mainstream opinions, the medical literature, and examples from extensive experience on the wards and in Court are discussed. Pediatric Forensic Evidence is aimed at doctors, lawyers, the Courts, social workers, health visitors, teachers, the police and others, guiding them through the analysis of injury and when to raise concerns.